AMPK-Dependent Metabolic Regulation by PPAR Agonists - Woo Hyung Lee; Sang Geon Kim (PPAR Research)
Comprehensive studies support the notion that the peroxisome proliferator-activated receptors, (PPARs), PPARα, PPARβ/δ, and PPARγ, regulate cell growth, morphogenesis, differentiation, and homeostasis. Agonists of each PPAR subtype exert their effects similarly or distinctly in different tissues such as liver, muscle, fat, and vessels. It is noteworthy that PPARα or PPARγ agonists have pharmacological effects by modulating the activity of AMPK, which is a key cellular energy sensor. However, the role of AMPK in the metabolic effects of PPAR agonists has not been thoroughly focused. Moreover, AMPK activation by PPAR agonists seems to be independent of the receptor activation. This intriguing action of PPAR agonists may account in part for the mechanistic basis of the therapeutics in the treatment of metabolic disease. In this paper, the effects of PPAR agonists on metabolic functions were summarized with particular reference to their AMPK activity regulation.